A single-phase bcc high-entropy alloy in the refractory Zr-Nb-Ti-V-Hf system. (15th July 2018) - Feuerbacher, M.; Lienig, T.; Thomas, C.
Abstract: We report on the production and characterization of a high-entropy alloy in the refractory Zr-Nb-Ti-V-Hf system. Equiatomic ingots were produced by arc and levitation melting, and were subsequently homogenized by high-temperature annealing. We obtained a coarse-grained, single-phase high-entropy alloy, with a homogeneous distribution of the constituting elements. The phase is a chemically disordered solid solution, based on a bcc lattice with a lattice parameter of 0.336(5) nm. Graphical abstract: Unlabelled Image